Ways of Dispersal of Nematodes of Heteroderidae Family - A. G. Babych; A. A. Babych (Российский паразитологический журнал, 2020)
The purpose of the research is study of the main sources and ways of dispersal of heteroderidae.Materials and methods. The research was conducted from 2002 to 2018 in Sumy, Chernihiv, Cherkasy, Poltava and other regions of Ukraine. The study of the features of the spatial dispersal of cyst nematodes in cultural and natural plant communities was carried out by the method of selection and analysis of plant and soil samples. Cysts from the soil were extracted by the flotation method. To determine the species composition of nematodes, temporary and permanent specimens were prepared according to generally accepted methods.Results and discussion. Wind erosion is one of the dominant sources of cysts dispersal. In natural biocoenosis, mole rats and moles are potential sources of the distribution of clover and other types of cyst nematodes. Among mouse-like rodents, representatives of the genus of gray voles are the most important, populating both cultural and natural plant communities. The dispersal of cysts can also occur in soil insects: bitterns, scarab beetles, carrion beetles, larvae of the May beetle, cut worms. However, the greatest dispersal of cysts occurs as a result of human activities. Cysts are also distributed by hand tools: shovels, rakes, hoes when performing various agricultural works on tillage. The implementation of a set of recommended technological operations for growing sugar and fodder beets leads to an increase in the area of existing foci within 90–170 cm, potatoes 75–125 cm, corn for green fodder and silage 30–85 cm, peas 18–55 cm, barley with clover seeding of 12–40 cm, winter cereal when using no-till and mini-till of 16–35 cm, and tail (plowing) and subsequent superficial 31–50 cm. The smallest up to 10 cm dispersal of cyst-forming nematodes was noted when growing perennial legumes in that due to the minimal number of mechanical operations for their maintenance.